Electro-morphological, structural, thermal and ionic conduction properties of Gd/Pr co-doped ceria electrolytes exhibiting mixed Pr3+/Pr4+ cations. Issue 4 (March 2019) - Spiridigliozzi, L.; Dell'Agli, G.; Accardo, G.; Yoon, S.P.; Frattini, D.
Abstract: Gd0.2-x Prx Ce0.8 O1.90, (x = 0, 0.02, 0.04, 0.06, 0.08, 0.10) has been synthesized by means of a simple co-precipitation route based on ammonium carbonate as the precipitating agent. The as-synthesized precursors are cerium-gadolinium-praseodymium amorphous hydroxycarbonates, which are nanometric in size with highly homogeneous morphology, leading to reactive doped and co-doped nanocrystalline (≈13 nm) ceria after a mild thermal treatment (2 h at 600 °C). The obtained results highlight the very positive effect of Pr on the powders' sintering behaviour, which favour a better densification of the final pellets, thus improving both their microstructure (with relative densities of 97–99% after sintering at 1250 °C for 3 h) and electrochemical properties (up to 1.25·10–1 S cm −1 at 800 °C for sample 6Pr) compared to the state-of-art ceria-based electrolytes. Through a comprehensive characterization, a relation was formed between the Pr content and the microstructural features of the sintered pellets and their electrical behaviour. The amount of Pr doping was investigated over a wide range and 6 mol% has been established to be optimal (possessing the lowest electronic conductivity contribution). Definitely, these results indicate that Gd0.2-x Prx Ce0.8 O1.90 has an excellent set of characteristics, both microstructural and electrical, and a convenient fabrication process, thus making it perfectly suitable for IT-SOFC practical applications. Graphical abstract: